The Impact of Digital Transformation in Land Services, Accountability, Organizational Culture, and Community Participation on Improving Service Quality at the Agrarian and Spatial Planning Office of the National Land Agency in Batam City - Pranoto, Sri (International Journal Labs, 2026)
This study aims to analyze the Influence of Digital Transformation of Land Services, Accountability, Organizational Culture and Community Participation on Improving Service Quality at the Agrarian and Spatial Planning Office of the National Land Agency of Batam City. This study uses a quantitative method with an explanatory research type, with a population of 169 and a research sample of 83 people determined by the Slovin formula (1960). The sampling technique used is simple random sampling where sampling is done randomly. Meanwhile, the data analysis method used in this study is simple linear regression analysis and multiple linear regression analysis. From the results of this study, it is evident that there is a positive and significant influence of partial variables on Service Quality Improvement, each Digital Transformation of Land Services. The magnitude of the influence of Anti-Corruption Behavior on the Professional Integrity of ASN is determined by the dimensions of Participation and Main Aspects. So that in the future, improving the quality of services should pay attention to the importance of the factors of Digital Transformation of Land Services, Accountability, Organizational Culture and Community Participation in the implementation and efforts to improve the quality of services so that it can run even better for the community, especially in an effort to improve the quality of services at the Agrarian and Spatial Planning Office of the National Land Agency in Batam City